Paulownia spp.: A Bibliometric Trend Analysis of a Global Multi-Use Tree - Linda Lugli; Giustino Mezzalira; Maurizio Lambardi; Huaxin Zhang; Nicola La Porta (Horticulturae, 2023)
The research on Paulownia spp. has increased in the last twenty years thanks to the growing interest in the application modalities of this plant in various sectors such as wood, phytoremediation, environmental protection, paper, biofuel, chemistry and medicine. For the first time, this study analyzed the papers present in the Web of Science Core Collection on “Paulownia” to obtain a set of characteristics in the work carried out from 1971 to 2021. This analysis selected and took into account 820 articles and provided evidence of the scientific production of authors, institutions, and countries. This work showed that the most studied species was Paulownia tomentosa, followed by P. fortunei and P. elongate. The JCR category and research area with the most publications was plant science, with 20.4% of the total. The papers were published in 460 journals and in a book series. The journals with the most publications were Bioresources, Advanced Material Research, Agroforestry Systems, Journal of Wood Science and Industrial Crops and Products. The institutions with the most prolific affiliation with the field of Paulownia spp. research were Henan University, the US Department of Agriculture, Belgrade University, the Chinese Academy, and Georgia University. Finally, the 3842 keywords were divided into nine different clusters and the trends of interest in the last fifteen years were highlighted.